الرأفة بالذات وعلاقتها بالمرونة النفسية لدى أمهات ذوي الإعاقة العقلية في محافظات غزة - النجار، مرفت عاطف جودت; المهدي، سمية الخليفة محمد (جامعة القدس المفتوحة, 2021)
هدف البحث الراهن إلى فحص مستوى الرأفة بالذات ومستوى المرونة النفسية لدى أمهات ذوي الإعاقة العقلية في محافظات غزة، فضلا عن استكشاف العلاقة بين كل من الرأفة بالذات، والمرونة النفسية لدى عينة الدراسة، بلغت عينة الدراسة (500) من أمهات ذوي الإعاقة العقلية في محافظات غزة من المترددات على (16) مركزا من مراكز تأهيل ذوي الإعاقة في غزة، تراوحت أعمارهن بين (19 -54) عاما؛ متوسط أعمارهن (33.48) عاما، بانحراف معياري (8.35)، حيث كان أقل مدى عمري (19) عاما، وأكبر مدى عمري (54) عاما. واستندت الدراسة على مقياسين: الرأفة بالذات، والمرونة النفسية وهما من (إعداد الباحثتين)، أشارت نتائج الدراسة إلى أن مستوى كل من الرأفة بالذات والمرونة النفسية وقعا ضمن المستوى المرتفع، كما وتبين وجود علاقة ارتباطية موجبة (طردية) بين الدرجة الكلية للرأفة بالذات والأبعاد الفرعية لها مع الدرجة الكلية للمرونة النفسية والأبعاد الفرعية له.
The current research aimed at examining the level of self-compassion and the level of psychological resilience among mothers with mental disabilities in the Gaza governorates. It also aimed at exploring the relationship between both self-compassion and psychological resilience with the study sample. The study sample consists of 500 mothers with mental disabilities in the governorates of Gaza, frequenting 16 rehabilitation centers for people with disabilities in Gaza; their ages ranged between 1954- years. Their average age was 33.48 years, with a standard deviation of 8.35 at the lowest age of 19 and the highest age of 54. The study was based on two measures: The self-compassion scale and the psychological resilience scale, which the researcher prepared. The results of the study indicated that the level of both self-compassion and psychological resilience occurred within the high level, and it was found that there is a positive (direct) correlation between the total degree of self-compassion and its sub-dimensions with the total degree of psychological resilience and its sub-dimensions.
Keywords: علم النفس التربوي -- التنشئة الاجتماعية -- المرونة النفسية -- الرأفة الذات -- ذوو الإعاقة العقلية